PENGARUH LIKUIDITAS, SOLVABILITAS DAN BIAYA BUNGA TERHADAP PROFITABILITAS DI KOPERASI SERBA USAHA SEDANA GRAHA SESETAN DENPASAR PERIODE 2013-2019 - Gusti Alit Suputra (Jurnal Ilmiah Manajemen & Bisnis, 2020)
This study aims to examine the effect of liquidity, solvency, and interest costs on profitability in the all-purpose cooperative Sedana Graha Sesetan Denpasar. This research was conducted using quantitative analysis techniques with multiple linear regression analysis, while to prove the hypothesis used the F test and t test techniques. The data collected is quantitative in the form of financial reports. The results showed that 1) the liquidity ratio measured by cash ratio has a significant negative effect on the profitability ratio, this means that the higher the level of cooperative liquidity, the lower the level of profitability achieved by KSU Sedana Graha Sesetan, because this can reduce the amount of profit so that disrupting cooperative operations, 2) the solvency ratio measured by debt to total assets has a significant positive effect on the profitability ratio, this means that the higher the level of the cooperative's solvency ratio, the higher the profitability ratio achieved by KSU Sedana Graha Sesetan, because this is short-term debt and the length of the company can be paid optimally by KSU Sedana Graha Sesetan, 3) Interest Expose Ratio measured by the interest exposure ratio has a negative and significant effect on the Profitability ratio, this means that the lower the Interest Cost ratio, the higher the Profitability ratio. s achieved by KSU Sedana Graha Sesetan. Because the higher the interest expense paid to customers, the less profit will be obtained by KSU Sedana Graha Sesetan. This research is expected to be a reference for Indonesian financial institutions, especially in the Sedana Graha Sesetan Business Savings Cooperative in identifying variables that can affect profitability, especially the Liquidity, Solvency, and Interest Costs ratio which can affect the profitability ratio of KSU Sedana Graha, in order to improve the financial quality of cooperatives. Keywords: Liquidity, Solvability, Interest Cost, Profitability